The Question of India’s Endangered Democracy in the Light of Intolerance Debate: Some Reflections - Abul Kalam Azad (Journal of Asian Social Science Research, 2022)
India is regarded as the world’s largest democratic country. The country is well known for its rich cultural diversity, pluralistic society and inclusive secular democracy. However, the recent political scenario has partially damaged the values of the liberal democracy of India. Since Narendra Modi became Prime Minister in 2014, the Bharatiya Janata Party (BJP) and its parental body Rashtriya Swayamsevak Sangha (RSS) have tried to accomplish their goal of Hindu Rashtra. Minorities in the country have been attacked, killed and deprived of their human rights. This article examines this trend by focusing on the growing intolerance during the Modi regime and its impact on the country’s democracy. It also discusses how the BJP at the central government and many other states, directly and indirectly, narrow down the space of civil society and media to fuel majoritarian agenda. Based on its findings, the article argues that in the Narendra Modi regime Indian political culture has been undergoing a shift from inclusive democracy to a narrow process of democracy. By doing so, it contributes to the studies on the rise of right-wing populism in some countries including India in the contemporary world.